OCT-Based Macular Structure-Function Correlation in Dependence on Birth Weight and Gestational Age : the Giessen Long-Term ROP Study - Bowl, Wadim; Stieger, Knut; Bokun, Magdalena; Schweinfurth, Silke; Holve, Kerstin; Andrassi-Darida, Monika; Lorenz, Birgit; Justus Liebig University Giessen (My University, 2016)
Abstract Purpose: To compare retinal layer thicknesses in preterm and term-born children using spectral-domain optical coherence tomography (SD-OCT) and to correlate structure with retinal function. Methods: We performed SD-OCT single and volume scans in the foveal region of premature children aged 6 to 13 years without ROP (no-ROP, n = 100) and with spontaneously regressed ROP (sr-ROP, n = 50) documented with wide-angle digital imaging during routine screening for acute ROP, and 30 age-matched term-born children. Retinal layer segmentation and analysis was performed with custom-made software in single and volume-scans using an Early Treatment of Diabetic Retinopathy Study grid-based method, and compared to light increment sensitivity (LIS) data obtained with a microperimeter at eccentricity points of 0°, 2.8°, and 8°, as previously described. Results: Overall, seven children had to be excluded due to poor image quality (n = 1 no-ROP; n = 2 sr-ROP; n = 4 term). Total retina, ganglion cell + inner plexiform layer (GCL+) and outer nuclear layer + external limiting membrane (ONL+) thickness at the foveal center in no-ROP and sr-ROP were significantly higher compared with term children. Gestational age (GA) and birth weight (BW) were inversely correlated with these layer thicknesses. Rod and cone outer segment length did not differ in either group. The ratio of ONL+ to the whole retina at 0° correlated significantly with reduced LIS. Conclusions: Increased thicknesses of the entire retina or specific layers at the fovea did not correlate with functional loss; but a thinner ONL in retinae without foveal pit did. This reduced ONL+ ratio is potentially caused by a reduced foveal cone density and may be the first morphologic functional correlate in prematurity and ROP.
Keywords: retinopathy of prematurity; birth weight; gestational age; spectral-domain optical coherence tomography; fundus-controlled perimetry; ddc:610